The Influence of Teacher’s Personality Competence, Curriculum, and School Climate on Student’s Morals - Ruslan Ruslan; Saparuddin Saparuddin; Husnaeni Husnaeni; Muhammad Alqadri Burga (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Modernization is a threat that can co-opt Islamic boarding schools from moral development to a formalistic orientation. The purpose of this study was to analyze the influence of teacher’s personality competencies, the curriculum, and the climate of Islamic boarding school on the students’ morals both partially and simultaneously. This type of research is a survey with a quantitative approach. The population of this study was 234 students, with 70 samples selected using the Yamane formula. Data collection methods using questionnaires and documentation. Data analysis using descriptive statistical and inferential statistical analysis techniques. The results showed that the teacher's personality competence, the curriculum, and climate of the Islamic boarding school had a positive and significant effect both partially and simultaneously on the students’ morals. This research has implications for the need for all members of Islamic boarding schools to be synergistically responsible for creating a conducive boarding school climate and culture. This conduciveness will develop moral values through various educational programs, especially curriculum and teacher competence developments.